Attenuated Duck Hepatitis A Virus Infection Is Associated With High mRNA Maintenance in Duckling Liver via m6A Modification - Wu, Liping; Quan, Weili; Zhang, Yi; Wang, Mingshu; Ou, Xumin; Mao, Sai; Sun, Di; Yang, Qiao; Wu, Ying; Wei, Yaxun; Jia, Renyong; Chen, Shun; et al. (Frontiers in Immunology, 2022)
Host translation is generally modulated by viral infection, including duck hepatitis A virus (DHAV) infection. Previously, we reported that cellular protein synthesis in a cell model of duck embryo fibroblasts is significantly inhibited by DHAV infection but not viral proteins, suggesting an important viral-host interaction occurs at the translational level. In this study, we aim to further understand the impact of DHAV virulence on cellular N6-methyladenosine (m6A) modification, which is essential to a wide variety of RNA biological processes, such as mRNA stabilization and translation. Using m6A antibody-based immunoprecipitation, m6A-seq, and LC–MS/MS, we observed that m6A-modified mRNA exists in both virulent and attenuated DHAV-infected duckling livers. Importantly, m6A levels in mRNA were much higher in attenuated DHAV-infected livers compared with virulent DHAV-infected livers, suggesting virulence-dependent regulation of m6A modification. Analysis of modification motifs indicated that GAAGAAG is the most enriched motif. Combined m6A-seq and RNA-seq data analysis indicated a generally positive correlation between m6A and mRNA expression levels in DHAV-infected duckling livers. GO analysis of genes with decreased or increased m6A levels showed that these genes were enriched in various terms, including oxidation–reduction processes and antiviral immune responses. Collectively, our work reveals DHAV virulence-dependent coordination between m6A modification and mRNA expression in duckling livers.